2017
DOI: 10.1007/s12207-017-9294-6
|View full text |Cite|
|
Sign up to set email alerts
|

Plausibility Judgments of Atypical Symptoms Across Cultures: an Explorative Study Among Western and Non-Western Experts

Abstract: Symptom validity tests (SVTs) are predicated on the assumption that overendorsement of atypical symptoms flags symptom exaggeration (i.e., questionable symptom validity). However, few studies have explored how practitioners from different cultural backgrounds evaluate such symptoms. We asked professionals working in Western (n = 56) and nonWestern countries (n = 37) to rate the plausibility of uncommon symptoms taken from the Structured Inventory of Malingered Symptomatology (SIMS), dissociative symptoms from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Our findings are in line with those of a previous study that found practitioners across different cultures to rate bizarre items taken from the SIMS as moderately plausible (Boskovic et al, 2017). The general tendency to give moderate plausibility rating even to the bizarre items might simply signal the idiographic approach practitioners and psychologists in training often take, which lowers their skepticism and encourages a "believe bias" or "truth bias" (see Beach & Taylor, 2017;Lilienfeld et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are in line with those of a previous study that found practitioners across different cultures to rate bizarre items taken from the SIMS as moderately plausible (Boskovic et al, 2017). The general tendency to give moderate plausibility rating even to the bizarre items might simply signal the idiographic approach practitioners and psychologists in training often take, which lowers their skepticism and encourages a "believe bias" or "truth bias" (see Beach & Taylor, 2017;Lilienfeld et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Previous cross-cultural research showed that psychologists in practice agree that items of SIMS are odd and rare, yet, their ratings also revealed moderate, rather than low, plausibility of such claims (Boskovic et al, 2017). Such findings indicate a tendency to take patients' claims at their face value or so-called truth bias (Beach et al, 2017), hence, a lack of skepticism (Lilienfeld et al, 2016) among practitioners.…”
Section: Introductionmentioning
confidence: 95%
“…Self-report scales that intend to measure the validity of symptom presentation have an even longer history and started with an early study of Hartshorne and May (1928; see also Ben-Porath, 2012). The idea behind these tests is that people who exaggerate their complaints will tend to over-endorse symptoms, even when these symptoms are extreme, bizarre, or quite rare across different cultures and settings (e.g., Boskovic, van der Heide, Hope, Merckelbach, & Jelicic, 2017). Next to validity scales embedded within standard measures of psychopathology, such as the Minnesota Multiphasic Personality Inventory-2 (MMPI-2; Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) and the Personality Assessment Inventory (PAI; Morey, 2007), several stand-alone instruments for detecting symptom over-reporting have been developed.…”
mentioning
confidence: 99%
“…The SIMS has satisfactory psychometric properties in various samples. In a recent meta-analysis on the cross-cultural assessment of feigning, the SIMS was found to possess high classification accuracy with low variability across cultures (Nijdam-Jones & Rosenfeld, 2017; see also Boskovic et al, 2017).…”
mentioning
confidence: 99%
“…A smaller body of research is associated with symptom validity tests (SVTs) than with PVTs, though in general, documented concerns related to biases associated with these measures involve cross-cultural diagnostic differences and unproven assumptions that signs of feigning are universal (Boskovic et al, 2017; Merten & Rogers, 2017). A meta-analysis by Nijdam-Jones and Rosenfeld (2017) found that of the available SVTs, the Structured Interview of Malingered Symptomatology (SIMS) had the best accuracy in assessing malingering in diverse populations.…”
Section: Pragmatic Practice Suggestionsmentioning
confidence: 99%